DECOLONISING OR AFRICANISATION OF THE THEOLOGICAL CURRICULUM: A CRITICAL REFLECTION - Knoetze, Hannes (Scriptura, 2021)
This article presents a critical reflection on the theological curricula at (South) African Universities’ faculties of theology (and religion) from a missional hermeneutic focusing on decolonisation or Africanisation. Realising that it is not sufficient merely to make a few alterations, this article takes a more practical and technical approach to amend the curricula to be more contextualised for Africa. The decolonisation or Africanisation challenge for a Faculty of Theology is three-fold: (i) to address content (African contextualisation); (ii) mode/s of delivery - Open Distance Learning (ODL) and (iii) Programmes and Qualification Mix (PQM) diversity (new programmes - diplomas and certificates). The question to which this article attends is this: what are the implications of decolonisation or Africanisation in a faculty of theology at an institution of higher education in (South) Africa?